Circus vs. Contemporary Fashion Shows Inspiration, Transpositions, and the Specificity of the Show - Ostrowska, Maria (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
Fashion shows are presentations of designer clothing collections, originally intended for a selected audience, including journalists, buyers, sponsors and celebrities. Thanks to the potential possibilities created by new technologies, such as online broadcasting or the immediate posting of pictures on the Internet, the contemporary fashion shows are no longer events for a hermetic group related to the fashion industry – they are now becoming extraordinary shows, shocking by the panache of artistic means of expression, their monumental stage designs and their excellent music, which are available to one and all. One of the most significant examples are Victoria’s Secret fashion shows, which have become famous due to their high-budget presentations and have been shaping the pop culture perception of fashion. The brand’s shows, which often draw on elements typical of the circus, clearly stand out against other fashion events. From the very beginning of its existence the circus has fulfilled basic cultural needs, appealed to common tastes and served as simple entertainment – it has always been a typically ludic part of culture. What meanings, from the perspective of anthropology of performances, does the use of the circus features in modern fashion shows convey?